Ethics briefings - Chrispin, Eleanor (Journal of medical ethics, 2010)
As previously reported here,1 Northern Ireland's governmental guidance, clarifying the circumstances in which abortion would be lawful, has been subject to judicial review. In November 2009, the High Court in Belfast ruled that the guidance should be withdrawn.2The court rejected claims that the guidance would lead to a situation where abortion was easier to obtain in Northern Ireland, and noted that the guidance outlined the law correctly and could not be considered a misdirection. The court requested, however, that the guidance be withdrawn as ‘those aspects…dealing with counselling and with conscientious objection…fail to give fully clear and accurate guidance’. It ruled that the guidance did not give healthcare professionals clear advice on what to do when approached by a woman concerned about the continuation of pregnancy but who did not satisfy the legal criteria to have an abortion. Concern was also expressed regarding advice given in the guidance on what a healthcare professional should do or is entitled to do when he or she takes the view that a proposed abortion would be unlawful.At the time of writing, the Department of Health, Social Services and Public Safety in Northern Ireland was reported to be ‘disappointed’ by the ruling and was considering the court's findings.3Three women from the Republic of Ireland challenged the country's restrictive abortion legislation at the European Court of Human Rights in December 2009.4 The women had all previously travelled to the UK for an abortion. One woman was a former alcoholic who feared that having another child would jeopardise her chances of being reunited with her children who had been placed into foster care. Another did not want to be a single parent. The third was in remission from cancer and was at increased risk of relapse due to pregnancy. …